Pain levels after total hip replacement: their use as endpoints for survival analysis. - Britton, A; Murray, D; Bulstrode, C; McPherson, K; Denham, R (1997)
We have assessed the relative value of various outcome measures after THR, by the analysis of follow-up data from over 2000 patients. They had been reviewed clinically and radiologically six months after operation, at one year, and then every two years, some for 16 years. At each review their pain level, stiffness and opinion of progress were scored and a radiograph taken. We found that pain level was the most informative outcome as a predictor of revision and correlated well with the patients' opinions. We made a comparison between the six types of implant in the series, using survival analysis and log-rank testing with different pain levels as endpoints. This analysis revealed differences which were not detected by survival analysis using the traditional endpoint of revision. We therefore recommend the use of different levels of pain as the main outcome measures after total hip replacement.